Implementasi Pengendalian Internal Berbasis Teknologi Informasi untuk Meningkatkan Integritas Data dan Memperkuat Mekanisme Fraud Detection - Lastianti, Siwidyah Desi (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
This study examines how the implementation of information technology within internal control systems enhances accounting information quality and strengthens fraud detection mechanisms. Using a qualitative literature review approach covering publications from 2015–2025, the study synthesises empirical findings on the role of digital accounting information systems in improving auditability, data reliability, and the mitigation of misstatement risk. The analysis indicates that IT integration reinforces the effectiveness of internal controls by increasing accuracy, timeliness, and transparency, while also providing more comprehensive audit trails for both internal and external auditors. However, digitalisation does not automatically guarantee stronger controls, as system design, user competence, and organisational readiness remain critical determinants of success. Overall, the study highlights that digital transformation in internal control represents a strategic pathway to improving data integrity and strengthening fraud mitigation in modern organisations.